Antibacterial Mouthwash of Kesum Leaf (Polygonum Minus Huds) Essential Oil on Streptococcus Mutans and Sanguinis - Sri Rezki; Halimah Halimah (JURNAL INFO KESEHATAN, 2020)
Polygonum Minus Huds methanol extract from several previous studies has antibacterial properties in bacteria in the mouth such as Streptococcus Mutans, Staphylococcus Aureus, Salmonella Typhi, Escherichia Coli, etc. The cause of gingivitis is Streptococcus Sanguinis and anaerobic bacteria in the subgingival, which is porphyromonas gingivalis. Polygonum Minus Huds has the potential to be an antibacterial mouthwash for bacteria that causes caries and gingivitis. This research aims to make a mouthwash based on the essential oil of Polygonum Minus Huds and determine its antibacterial properties in mouthwashes of 0.025% and 0.05% concentrations to find antibacterial activity on Streptococcus Mutans and Sanguinis. The research was conducted in June 2019 at the Chemistry Laboratory of Faculty of Mathematics and Natural Sciences, the University of Tanjungpura in Pontianak Lab and Health Polytechnique Pontianak Integrated Lab. Design Quasi-experimental research used post-test only control group design, mouthwash formulation with essential oil concentrations of 0.025% and 0.05%, positive control using non-alcoholic mouthwash, and negative control (Aquades). Statistical analysis was performed univariately. The results showed that the best mouthwash was 2.5 ml of Tween 80 and 2.5 ml of glycerin. The results showed the essential oil gargle of Kesum leaves (Polygonum Minus Huds) at concentrations of 0.05%, and 0.02%, which is the bacteria of Streptococcus Mutans and Streptococcus Sanguinis were not able to inhibit the growth of the two bacteria. Increasing the amount of concentration or making mouthwash in other forms is expected to increase its antibacterial effect.